Prevalence and associated factors of cross-sectional and incident self-reported arthritis or rheumatism among a national community sample of middle-aged and older adults in Thailand - Pengpid, Supa; Peltzer, Karl (Frontiers in Public Health, 2023)
Background: The study aimed to assess the prevalence and associated factors of cross-sectional and incident arthritis or rheumatism among a national community sample of middle-aged and older adults in Thailand. Methods: We analyzed cross-sectional and longitudinal data from two consecutive waves (2015 and 2017) of the Health, Aging, and Retirement in Thailand (HART) study. Arthritis or rheumatism (SRA) was assessed by self-reported health care provider diagnosis. Results: The cross-sectional (baseline) sample included 5,616 participants (≥45 years, median age 66 years, interquartile range 57 to 76 years) and the incident (follow-up) sample included 3,545 participants. The prevalence of SRA in the cross-sectional sample (baseline) was 4.0% and in the incident (follow-up) sample 5.3%. In the cross-sectional multivariable model, obesity class I (aOR: 1.78, 95% CI: 1.19 to 2.67), obesity class II (aOR: 1.82, 95% CI: 1.02 to 3.25), hypertension (aOR: 1.90, 95% CI: 1.35 to 2.66), brain disease and/or psychiatric problems (aOR: 4.79, 95% CI: 2.27 to 10.62), sleep problem (aOR: 1.45, 95% CI: 1.01 to 2.07) and prescription drug use (aOR: 1.63, 95% CI: 1.14 to 2.33) were positively associated, and not in the labour force (aOR: 0.53, 95% CI: 0.34 to 0.84), and employed (aOR: 0.63, 95% CI: 0.41 to 0.99) were negatively associated with SRA. In the incident multivariable model, obesity class I (aOR: 1.78, 95% CI: 1.17 to 3.61), obesity class II (aOR: 2.01, 95% CI: 1.12 to 3.61), poor mental health (aOR: 1.69, 95% CI: 1.19 to 2.41), and functional disability (aOR: 2.04, 95% CI: 1.01 to 4.13) were positively associated, and current alcohol use (aOR: 0.50, 95% CI: 0.25 to 0.99) was negatively associated with SRA. Conclusion: The middle and older Thai adults had a low prevalence and incidence of SRA, and several physical and mental risk factors for cross-sectional and/or incident SRA were identified.